Development and Initial Psychometrics of Counseling Supervisor's Behavior Questionnaire. (July 2016) - Lee, Ahram; Park, Eun Hye; Byeon, Eunji; Lee, Sang Min
This study describes the development and psychometric properties of the Counseling Supervisor's Behavior Questionnaire, designed to assess the specific behaviors of supervisors, which can be observed by supervisees during supervision sessions. Factor structure, construct and concurrent validity, and internal consistency reliability of the Counseling Supervisor's Behavior Questionnaire scores are reported, along with a discussion of the implications for practice in supervision.